Nurse Staffing, Mortality, and Length of Stay in For-Profit and Not-for-Profit Hospitals - Barbara A. Mark; David W. Harless (SAGE Publishing, 2007)
The issue of differential quality in for-profit (FP) and not-for-profit (NFP) hospitals remains a critical health policy question. With research demonstrating a relationship between nurse staffing and quality, the question arises whether the relationship differs in these hospital types. Using Healthcare Cost and Utilization Project data from the period 1990-1995, we found that case mix-adjusted registered nurse (RN) staffing was significantly lower in FPs than in NFPs, and we found a superior distribution of outcomes (mortality and length of stay) obtained with a lower level of RN staffing. The differences in mortality and length of stay disappeared, however, after controlling for population and market characteristics.